2018
DOI: 10.1007/s10955-018-2108-8
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptive Sampling of Large Deviations

Abstract: We introduce and test an algorithm that adaptively estimates large deviation functions characterizing the fluctuations of additive functionals of Markov processes in the long-time limit. These functions play an important role for predicting the probability and pathways of rare events in stochastic processes, as well as for understanding the physics of nonequilibrium systems driven in steady states by external forces and reservoirs. The algorithm uses methods from risk-sensitive and feedback control to estimate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 64 publications
(179 reference statements)
0
73
0
Order By: Relevance
“…This is because, for the parameters considered in our numerical study, heat fluctuates much more than work, as already suggested by the moments and cumulants shown in Fig. 6b and c. Let us note that while we have computed the LDFs using the standard BD, which was much more time consuming than the evaluation of the MNM, there are various optimized simulation algorithms [45][46][47] for computing of LDFs that can render BD simulations more competitive.…”
Section: B Moment Generating Functionsmentioning
confidence: 73%
See 1 more Smart Citation
“…This is because, for the parameters considered in our numerical study, heat fluctuates much more than work, as already suggested by the moments and cumulants shown in Fig. 6b and c. Let us note that while we have computed the LDFs using the standard BD, which was much more time consuming than the evaluation of the MNM, there are various optimized simulation algorithms [45][46][47] for computing of LDFs that can render BD simulations more competitive.…”
Section: B Moment Generating Functionsmentioning
confidence: 73%
“…For the parts of the piece-wise constant protocol with time-independent potential, the tilted matrices can also be computed from the formula (47).…”
Section: B Moment Generating Functionsmentioning
confidence: 99%
“…In practice, the driving protocol should simply mimic the biased noise realizations. This line of thought has already been exploited for efficient sampling of the biased ensemble [65,[114][115][116], where control forces make rare events become typical. Moreover, since our analytic framework encompasses the case of a specific bias for each pair of particle, it could potentially be regarded as a fruitful route to promote the spontaneous self-assembly of complex structures at the cost of energy dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results also open a direction of research to characterise fluctuations in a given system by engineering a new system subjected to an additional external force. Such an approach has been used in recent studies on adaptive algorithms, based for instance on a feedback procedure to evaluate the effective force [66,67,68,69], improving the computational efficiency. The weak-noise regime has been seldom studied (it is in fact know to present specific difficulties [66]), and the results we present in this paper could help to understand large-time fluctuations and their associated phenomenology both in experiments and simulations.…”
Section: Discussionmentioning
confidence: 99%